2015
DOI: 10.1002/pbc.25606
|View full text |Cite
|
Sign up to set email alerts
|

Relapse and outcome patterns of patients with central nervous system mixed malignant germ cell tumors treated without irradiation: Findings from the Third International Central Nervous System (CNS) Germ Cell Tumor (GCT) Study

Abstract: Patients with CNS MMGCT relapsing following chemotherapy alone display two distinct patterns of recurrence and outcome; patients relapsing early possess MMGCT elements and have a dismal prognosis, while patients relapsing late do so with pure germinomatous elements and have an excellent outcome. Current cooperative group studies utilizing more localized fields of irradiation should monitor closely the patterns of relapse and outcome; late recurrences with germinomatous elements might be avoided by initial use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Few studies have explored different approaches to patients with relapsed CNS‐NGGCT. Only 14 of 63 patients (22%) with relapsed CNS‐NGGCT documented in four major studies were reported as long‐term survivors . Published therapeutic strategies for relapsed CNS‐NGGCT are summarized in Table …”
Section: Treatment Of Recurrent Cns‐nggctmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have explored different approaches to patients with relapsed CNS‐NGGCT. Only 14 of 63 patients (22%) with relapsed CNS‐NGGCT documented in four major studies were reported as long‐term survivors . Published therapeutic strategies for relapsed CNS‐NGGCT are summarized in Table …”
Section: Treatment Of Recurrent Cns‐nggctmentioning
confidence: 99%
“…Murray et al analyzed retrospectively 45 patients with relapsed CNS‐NGGCT; none of the 10 patients who received only standard dose platinum‐based chemotherapy for relapse survived compared with 3 of 16 who were treated with HDCx/AuHCR . Several studies have suggested that HDCx/AuHCR improves outcomes among patients with relapsed/refractory CNS‐NGGCT . However, the findings of these studies might be confounded by various limitations: retrospective study design, small sample size, selection bias, not receiving any radiotherapy at initial diagnosis, and variable first‐line treatments .…”
Section: Treatment Of Recurrent Cns‐nggctmentioning
confidence: 99%
See 1 more Smart Citation
“…RT has become standard of care for both germinomas and NGGCTs due to the high risk of relapse with chemotherapy alone. Multiple studies have been conducted looking at the use of chemotherapy alone in CNS GCTs with unacceptable progression‐free survival (PFS) rates of 36–50% . A dramatic improvement was seen with the use of multimodal therapy combining chemotherapy with craniospinal irradiation (CSI) of 36 and 54 Gy total to the primary site .…”
Section: The Role Of Rtmentioning
confidence: 99%
“…NGGCTs require aggressive multidisciplinary treatment involving combinations of chemotherapy, surgery, and radiotherapy. Chemotherapy‐only protocols have demonstrated unacceptable rates of failure, as have radiotherapy‐only protocols . Strategies utilizing reduced‐field radiotherapy with induction chemotherapy have demonstrated potential in maintaining acceptable survival rates, while reducing late toxicity .…”
Section: Introductionmentioning
confidence: 99%